Preparation and characterization of SO3-doped barium borosilicate glass-ceramics containing zirconolite and barite phases. Issue 1 (January 2017) - Wang, Xin; Wu, Lang; Li, Huidong; Xiao, Jizong; Cai, Xin; Teng, Yuancheng
Abstract: In order to improve the solubility of actinides and sulfate in the glass matrix, barium borosilicate glass-ceramics containing zirconolite and barite crystalline phases were developed. The effects of SO3 addition (0–8 wt%) on crystalline phases, microstructure, and chemical durability of glass-ceramics belonging to SiO2 -B2 O3 -Na2 O-BaO-CaO-TiO2 -ZrO2 -Nd2 O3 -SO3 system were mainly studied. The results show that glass transformation temperature decreases slightly with increasing SO3 content. The main crystalline phase is zirconolite for all of the samples. When the addition SO3 content is higher or equal to 4 wt%, rice-shaped barite crystals appear in the bulk of glass-ceramics. Barite phase was formed during the melting stage. X-ray fluorescence analysis indicates that about 1.3 wt% of SO3 can be incorporated in the glass-ceramics when the addition content of SO3 is 6 wt%. S element mainly distributes in the barite crystals. The decomposition of sulfate mainly occurs during the melting process. Moreover, the addition of a certain content (≤6 wt%) of sulfate has no significant influence on the chemical durability of barium borosilicate glass-ceramics.